Didactic and Innovative Activities for English Language Teachers - Chavez, Jessica; Murga, Norma; Castro, Max (CIEX JOURNAL, 2016)
Didactic activities contribute to promote the students´ capacities, assisting them to develop their abilities. This research presents a proposal of didactic innovative and communicative activities for language teachers when applying CIEX Methodology to motivate students. The main contribution of the research is a proposal for implementing language teaching activities to enhance pupils' language learning process by assessing their communicative competence. The considerations of each language teachers are vital for this proposal. Therefore, this research has been gathering information from students and teachers using both: qualitative and quantitative research techniques.